Exploring Knowledge Development for Sustaining the Intellectual Capital of Technical and Vocational Education and Training leadership Research: A Qualitative Study At a Global South University - Ferdinand-James, Debra; Nelson, Karlene; Bishop, Natalie (Yayasan Nurul Yakin Bunga Tanjung, 2024)
A Caribbean University in the Global South is committed to sustaining Technical and Vocational Education and Training (TVET)